2019
DOI: 10.1186/s12879-019-4610-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile, risk factors and antimicrobial susceptibility patterns of symptomatic urinary tract infection among students of Mekelle University, northern Ethiopia

Abstract: BackgroundBacterial infection of the urinary tract is among the common reasons for seeking medical attention in the community. Rapidly increasing antibiotic resistance of uropathogens is resulting in limited treatment options. Therefore, knowledge of the current uropathogens and their antibiotic susceptibility is important for better treatment of urinary tract infection.MethodsA cross-sectional study design was conducted from February to September thirty, 2017 among students who came to Mekelle University stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

35
82
5
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(127 citation statements)
references
References 29 publications
35
82
5
5
Order By: Relevance
“…The increasing frequency of prostate disease and diabetes mellitus in males are responsible for the increase in the the incidence of UTI in elderly patients. This report is similar to some studies [31,16] in chich a prevalence of 23.3% was reported in females aged 26-30 years, and in disagreement with another study that showed that female patients within the age range 37-47 years had the highest prevalence rate of 46.2%, followed by 26-36 years (31.1%), 15-25 years (18.2%) and above 48 years of age, showed the lowest prevalence of 4.5%, while among the male patients, 37-47 years showed the highest prevalence rate of 51.3%, followed by 26-36 years (29.5%), 15-25 years (14.1%), and above 48 years of age showed the lowest (5.1%) [25]. Statistical analysis showed that there was no significant difference between age and gender at 5% (P < 0.05).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The increasing frequency of prostate disease and diabetes mellitus in males are responsible for the increase in the the incidence of UTI in elderly patients. This report is similar to some studies [31,16] in chich a prevalence of 23.3% was reported in females aged 26-30 years, and in disagreement with another study that showed that female patients within the age range 37-47 years had the highest prevalence rate of 46.2%, followed by 26-36 years (31.1%), 15-25 years (18.2%) and above 48 years of age, showed the lowest prevalence of 4.5%, while among the male patients, 37-47 years showed the highest prevalence rate of 51.3%, followed by 26-36 years (29.5%), 15-25 years (14.1%), and above 48 years of age showed the lowest (5.1%) [25]. Statistical analysis showed that there was no significant difference between age and gender at 5% (P < 0.05).…”
Section: Discussionsupporting
confidence: 94%
“…The study also showed a higher incidence of urinary tract infection in females than males. The results obtained are similar to those in other studies reported in Nigeria [27,16,28] and in Yemen [29]. The high prevalence of infection in females is usually related to anatomical and pathogenic factors, such as the short length of the urethra, hence a shorter distance for bacteria ascending up the tract, hormonal changes affecting the adherence of bacteria to the mucosa, and urethra trauma during sexual intercourse.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations